O mercado das diversões no distrito de Carmo da Mata, Minas Gerais (1888-1920) - Edimar Reni Anísio (2023)
Research into the history of leisure in Brazil's smallest and mostly rural districts still remains scarce. In an effort to broaden this universe of references, this paper analyzes the historical dynamics of the amusement market in Nossa Senhora do Carmo da Mata, at the time a small district in the city of Oliveira. Based on the almost archaeological work of gathering fragments of information about the township published in local newspapers, agricultural questionnaires, statistical censuses, works by memoirists and criminal proceedings, we present a historical interpretation of the nature of the social dynamics of leisure time in a small rural nucleation in Minas Gerais in the transition between the 19th and 20th centuries, a fact little considered in studies on the topic. Throughout this work, we have observed how the development of the rural economy and its implications in terms of increased revenue, population growth and salaried labor, the boosting of city businesses and the expansion of entertainment opportunities in the district of Carmo da Mata between 1888 and 1920 were articulated. Ultimately, we found this broadening of entertainment options with the addition of cinema, theater, billiards and soccer, which added to its diversification.